1994
DOI: 10.1002/cne.903500307
|View full text |Cite
|
Sign up to set email alerts
|

Mu, delta, and kappa opioid receptor mRNA expression in the rat CNS: An in situ hybridization study

Abstract: The mu, delta, and kappa opioid receptors are the three main types of opioid receptors found in the central nervous system (CNS) and periphery. These receptors and the peptides with which they interact are important in a number of physiological functions, including analgesia, respiration, and hormonal regulation. This study examines the expression of mu, delta, and kappa receptor mRNAs in the rat brain and spinal cord using in situ hybridization techniques. Tissue sections were hybridized with 35S-labeled cRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

59
480
6
11

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 781 publications
(556 citation statements)
references
References 103 publications
(98 reference statements)
59
480
6
11
Order By: Relevance
“…[12][13][14] Interestingly, the m-opioid receptor (m-R) is enriched in these sites. 175 Melanocortins can antagonize the addictive properties of opiates and can provoke signs analogous to those by opiate withdrawal in drug-naive animals. 13,176 In addition, b-endorphin, like a-MSH and g-MSH, is cleaved from POMC, 13,70,177 suggesting that the endogenous opioid peptide and melanocortins may be coreleased.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Interestingly, the m-opioid receptor (m-R) is enriched in these sites. 175 Melanocortins can antagonize the addictive properties of opiates and can provoke signs analogous to those by opiate withdrawal in drug-naive animals. 13,176 In addition, b-endorphin, like a-MSH and g-MSH, is cleaved from POMC, 13,70,177 suggesting that the endogenous opioid peptide and melanocortins may be coreleased.…”
mentioning
confidence: 99%
“…Interestingly, the PAG receives melanocortin inputs and expresses MC4-R mRNA and m-R mRNAs. 77,79,80,107,175 In addition, the PAG is more deeply implicated in morphine dependence than is the VTA. 179 Collectively, it is attractive to speculate that melanocortinergic agents may be effective in treating addiction.…”
mentioning
confidence: 99%
“…Naloxone is generally regarded as a relatively nonselective opioid receptor antagonist, but research has shown that at low doses, its effects are primarily mediated through mu receptors [68]. These receptors are highly localized within the NAc, VP, and BLA, and their activities have been previously shown to affect both hedonic and motivational processes related to food consumption [12,19,22,26,28,34,35,69]. Future research focusing on central manipulations will prove fruitful to our understanding of this topic.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous opioid system (EOS) consists of a number of opioid peptides and their respective receptors, distributed throughout a number of central and peripheral tissues [12][13][14][15]. EOS involvement in a number of biological processes that include analgesia, hormone regulation, motor function, motivation, and hedonic processing can likely be attributed to their vast localization in the brain and periphery [10,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…e.g. ÎĽ-opioid receptors (in NTS and DMNV) [157], cannabinoid receptors (CB 1 -receptors in NTS and DMNV and CB 2 -receptors in NTS and brain stem neurons) [158,159] NK 1 -receptors in NTS and DMNV) [160,161], angiotensin AT 1 receptors in in the NTS, area postrema and DMNV [162,163] can influence gastric mucosal homeostasis. Our experimental results demonstrated that opioid peptides [4,133], anandamide, 2-arachidonoyl glycerol (2-AG) endocannabinoids, ligands of cannabinoid CB 1 and CB 2 receptors [137,142], as well as (SP) [136] given i.c.v.…”
Section: Role Of Capsaicin Sensitive Afferent Fibers and In The Actiomentioning
confidence: 99%